First report of anthelmintic resistance in gastrointestinal nematodes of sheep from Costa Rica - Maroto, R (2011)
As the prevalence and severity of anthelmintic resistance continue to rise, nematode infections in sheep correspondingly reduce the profitability of the sheep industry. In Costa Rica, sheep production systems are increasing in both number and importance. A field trial study was carried out to detect the level of anthelmintic resistance to albendazole and ivermectin in gastrointestinal nematodes (GIN) of sheep from seven farms in Costa Rica. Resistance was determined using the fecal egg count reduction test (FECRT). Three treatment groups were assessed on each farm: control, albendazole, and ivermectin. Haemonchus spp. (71%), Strongyloides sp. (57%), and Trichostrongylus spp. (43%) presented resistance levels to albendazole, whereas Strongyloides sp. (43%), Haemonchus spp. (29%), and Trichostrongylus spp. (29%) were resistant to ivermectin. Haemonchus spp., Strongyloides sp., and Trichostrongylus spp. were the most resistant GIN to both products. This study suggests that frequency of treatment, exclusive chemical control, and visual estimation of animal weight to calculate dosage may contribute to the high levels of anthelmintic resistance that were observed on the farms analyzed herein.